Upaya Peningkatan Kompetensi Calon Akuntan dalam Menghadapi Era Pembangunan Berkelanjutan Melalui Pemahaman Konsep Akuntansi Sosial dan Lingkungan - Wijayanti, Rita; Sari, Shinta Permata; Kurniawati, Lintang (Prosiding University Research Colloquium, 2022)
This community service activity is intended for students of the Accounting Program FEB UMS as future accountants. The absence of the course that specifically study about social and environmental accounting and the limited of textbook are a separate obstacle for students of the Accounting Program FEB UMS to have future accountang competencies that can meet market needs. This community service activity was carried out on Saturday, June 26, 2021 online through the Google meet applications. The service method carried out is in the form of an explanation of current current accounting issues, global solutions to overcome social and environmental crises, transformation to green accounting, theory and practice towards green accounting, challenges and opportunities for the accounting profession. The material is not only presented in the form of theory, but also case studies on how to apply social and environmental accounting in reporting. This is done so that students get an idea of the difference between conventional accounting and the application of social and environmental accounting.